1976
DOI: 10.4319/lo.1976.21.4.0540
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical formulation of the relationship between photosynthesis and light for phytoplankton

Abstract: Eight different mathematical formulations of the photosynthesis-light curve for phytoplankton (up to and including light saturation) were recast in terms of the same two parameters : the initial slope CY, and the assimilation number P,fiD. Each equation was tested for its ability to describe empirical data from natural populations of marine phytoplankton:the results of 188 light-saturation experiments at three coastal locations in Nova Scotia over a 2-year period.The most consistently useful mathematical repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
1,116
2
10

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,799 publications
(1,166 citation statements)
references
References 10 publications
11
1,116
2
10
Order By: Relevance
“…The initial slope of the P vs I plots, a, and the photosynthetic capacity, P,,,, were derived from a hyperbolic tangent fit (Jassby & Platt 1976) through 12 or more data points. Oxygen flash yields (PSUo,) were measured with repetitive short (< 3 vs) xenon flashes (GenRad Stroboslave 1539A) with a Rank Brothers electrode as described by Falkowski et al (1981).…”
Section: Methodsmentioning
confidence: 99%
“…The initial slope of the P vs I plots, a, and the photosynthetic capacity, P,,,, were derived from a hyperbolic tangent fit (Jassby & Platt 1976) through 12 or more data points. Oxygen flash yields (PSUo,) were measured with repetitive short (< 3 vs) xenon flashes (GenRad Stroboslave 1539A) with a Rank Brothers electrode as described by Falkowski et al (1981).…”
Section: Methodsmentioning
confidence: 99%
“…The photosynthesis versus irradiance curves (P vs I curves) were fitted to the data according the Jasby and Platt model [25]. When photoinhibition occurred, the model of Platt et al [38] was used.…”
Section: Sampling Sitementioning
confidence: 99%
“…P max , E k , and a have been estimated from the fitting of AGP versus light intensity with the model of Jasby and Platt [25] (see Methods). The highest a (0.106 mol O 2 mol photons )1 ) was observed for the rnicrobialite sampled at 19 m depth (Phormidium sp.…”
Section: Oxygen Processes Under Various Light Intensitiesmentioning
confidence: 99%
“…There were several studies on the relationships between the light or light combined with other factors and phytoplankton growth (Jassby and Platt, 1976;Mur et al, 1977;Huisman and Weissing, 1994;Litchman, 1998;Flder and Burns, 2005;Carneiro et al, 2009;Chen et al, 2009a;Mehnert et al, 2010;Kunath et al, 2012), however, the general results and conclusions from most of these studies were conducted only in laboratory and need to be further confirmed under field conditions. In the literatures, light shading was occasionally used for the control of phytoplankton in drinking water sources (Kojima, 2000;Chen et al, 2009b;Wan and Zhu, 2009).…”
Section: Introductionmentioning
confidence: 99%